2021
DOI: 10.3389/fgene.2021.783826
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst Morphology Based on Uniform Time-Point Assessments is Correlated With Mosaic Levels in Embryos

Abstract: Avoiding aneuploid embryo transfers has been shown to improve pregnancy outcomes in patients with implantation failure and pregnancy loss. This retrospective cohort study aims to analyze the correlation of time-lapse (TL)-based variables and numeric blastocyst morphological scores (TLBMSs) with different mosaic levels. In total, 918 biopsied blastocysts with time-lapse assessments at a uniform time-point were subjected to next-generation sequencing–based preimplantation genetic testing for aneuploidy. In consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Due to the observational nature of retrospective studies, it should not be assumed that there is a causal relationship between the euploidy of the embryo with the status of the polar body; controlled experiments need to be carefully designed before providing clinical recommendations. In this study, we retrospectively evaluated the status of polar body and euploidy of embryo that could be considered for transfer by next-generation sequencing (NGS) analysis among patients undergoing preimplantation genetic testing (PGT) treatment ( Chen et al, 2021 ) between January 2020 and December 2021 at the Reproductive Medicine Center of Tongji Hospital. Only embryo biopsies in fresh cycles were considered to eliminate the effects of vitrification.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the observational nature of retrospective studies, it should not be assumed that there is a causal relationship between the euploidy of the embryo with the status of the polar body; controlled experiments need to be carefully designed before providing clinical recommendations. In this study, we retrospectively evaluated the status of polar body and euploidy of embryo that could be considered for transfer by next-generation sequencing (NGS) analysis among patients undergoing preimplantation genetic testing (PGT) treatment ( Chen et al, 2021 ) between January 2020 and December 2021 at the Reproductive Medicine Center of Tongji Hospital. Only embryo biopsies in fresh cycles were considered to eliminate the effects of vitrification.…”
Section: Methodsmentioning
confidence: 99%
“…We discovered differences in the distribution of embryo morphological classification among the euploid and aneuploid groups. Individual morphological components adopted in blastocyst evaluation (i.e., expansion degrees, inner cell mass grades, and trophectoderm grades) have been independently correlated with euploid/aneuploid status ( 17 , 18 ). Considering the grade of expansion, grade 3 represented the most common value across all groups; however, we found significant differences in this distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the grade of expansion, grade 3 represented the most common value across all groups; however, we found significant differences in this distribution. Chen et al indicated a greater likelihood of euploidy among blastocysts with good-quality inner mass cell or trophectoderm morphology ( 17 ). Similarly, most euploid embryos had grade A inner mass cell morphology, while grade B represented the most observed grade for aneuploidies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ]. Another retrospective cohort study by Chen et al used multivariate generalized estimating equation analysis to evaluate the correlation of time-lapse-based variables and numeric blastocyst morphological scores with different mosaic levels (≤ 20%, ≤ 50% and ≤ 80%) in 918 biopsied blastocysts and suggested that blastocyst morphokinetic are significantly correlated with the threshold levels of mosaicism[ 28 ]. The correlation between blastocyst morphology and the mosaicism level is unclear.…”
Section: Discussionmentioning
confidence: 99%